Combined effect of exfoliated graphite/ferrite filled epoxy composites on microwave absorbing and mechanical properties - Shubham Mishra; Vivek Pratap; Ashwani Kumar Chaurasia; Amit Kumar Soni; Ashish Dubey; Alok Kumar Dixit (Physics Open, 2023)
Radar absorbing structural (RAS) composites are laminate with a low reflection coefficient for the electromagnetic illumination in microwave frequency range, and thus it can be used in the civil and stealth applications. In this study, a series of Exfoliated Graphite (EG) in combination with U-type barium hexaferrite based epoxy composites was fabricated with varying weight percentages (0.25, 0.50, 0.75 and 1.00 wt%) of EG and fixed wt.% (60 wt%) of U-type hexaferrite through wet mixing and compression moulding technique. Here, Raman spectra shows the EG to be defect-free characteristics. Subsequently, prepared composites were measured for microstructure and electromagnetic (EM) properties in 8.2–12.4 GHz frequency range (X-band). Further, complex permittivity (εr = ε′−jε″) and complex permeability (μr = μ′−jμ″) of the designed composites were measured using Vector Network Analyzer (VNA). Designed EG/hexaferrite-epoxy composite shows maximum real permittivity and permeability values (ε′ = 18.90 and μ′ = 0.91) for 3.3 mm thickness with minimum reflection loss −8.43 dB with 0.75 wt % EG filled (Sample-3)in X-band. While, it can withstand the different mechanical forces and shown the better absorption mechanism.EG plays important role due to their unique properties with optimize loading percentages in ferrite-epoxy composites. It may be concluded that, optimized EG/hexaferrite based composites determine as good microwave absorber in 8.2–12.4 GHz frequency ranges. Consequently, the prepared structural composites can be used to design the microwave absorbers and electromagnetic interference (EMI) shields for stealth applications.